Pengaruh Lingkungan Belajar dan Dukungan Sosial Terhadap Academic Burnout Siswa SMA AL-ISLAM KRIAN - Agatha, Putri Alifia Julia; Pamungkas, Heni Purwa (UIR Press, 2024)
Academic burnout or academic fatigue is a condition of fatigue in learning that is often experienced by several individuals, especially students. The causes of academic burnout include the learning environment and social support. This study aims to analyze 1) the influence of the learning environment on academic burnout of Al-Islam Krian High School students, 2) the influence of social support on academic burnout of Al-Islam Krian High School students, 3) the influence of the learning environment and social support on academic burnout of Al-Islam Krian High School students. This study uses a quantitative method with multiple linear regression data analysis techniques through the assistance of SPSS software version 22. The sample used was 222 students from class X of Al-Islam Krian High School, with a simple random sampling technique using the slovin formula. The results of this study indicate that: 1) there is no significant influence between the learning environment on academic burnout of Al-Islam Krian High School students, 2) there is a significant influence between social support on academic burnout of Al-Islam Krian High School students, 3) there is a significant influence between the learning environment and social support on academic burnout of Al-Islam Krian High School students